Psoriasis Relationship with Hypertension in Psoriasis Patients at RSI Jemursari Surabaya - Retna Gumilang; Meidyta Sinantryana Widyaswari; Zakiyyatur Rizkiyyah Husin (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Abstract. Background: Psoriasis is a chronic inflammatory disease of the skin that characterized by firmly bound erythema plaques covered in thick squama and caused by multiple abnormalities of genetic, biochemical, immunologic, vascular with further severed by various other factors such as psychology, drugs, smoking, and alcohol consumption. Several studies revealed that psoriasis can increase the risk of cardiovascular diseases such as hypertension, however, the underlying pathophysiological mechanism has not been confirmed yet. This mechanism is probably attributed to increased levels of angiotensin-converting enzyme produce angiotensin II that regulates vascular tonus, endothelin-1 (ET-1) has been considered an important role in that vasoconstrictor proteins are potent, and increased plasma renin activity has been reported in patients with psoriasis. Purpose: In order to figure out the relationship between psoriasis and hypertension in psoriasis patients at the Outpatient Unit -RSI Jemursari Surabaya.  Methods: This study was observational analytics with cross sectional study design in 28 psoriasis patients at Outpatient Unit-RSI Jemursari Surabaya during 2017-2019, using total sampling technique. Secondary data from medical records was collected and further analyzed with spearman correlation tests. Result: The obtained significance value is 0.000 (p < 0.05), which represent a significant relationship between hypertension and psoriasis. the correlation coefficient is 0.757, which indicates the strength of a strong relationship between two variables. Conclusion: There is a significant association between Psoriasis and Hypertension.